ANALISIS KEAMANAN SITEM INFORMASI AKADEMIK FAKULTAS ILMU KOMPUTER INSTITUT TEKNOLOGI & BISNIS LEMBAH DEMPO MENGGUNAKAN FRAMEWORK COBIT 5 - Effendi, Muhammad Junius; Prakarsya, Agustian (Universitas Lembah Dempo, 2021)
Information system security is very important to maintain the validity and integrity of data and ensure the availability of services for its users. COBIT Framework - COBIT is an IT governance guide framework and or can also be referred to as a supporting toolset that can be used to bridge the gap between needs and how technically it is to fulfill these needs in an organization. COBIT provides a framework guide that can control all organizational activities in detail and clearly so that it can help facilitate decision making at the top level in the organization. The Institute of Technology & Business (ITBis) is one of the educational institutions that relies most of its teaching process on information systems, and information technology as a means and infrastructure to provide services to students, lecturers and all staff as well as assist the implementation of activities in all existing units.